Food Bioactives: Impact on Brain and Cardiometabolic Health - Findings from In Vitro to Human Studies - Naumovski, Nenad; Sergi, Domenico (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The search for dietary patterns or food bioactive derivatives that may serve as a panacea for health issues has been a topic of interest for several millennia. It is not surprising that this trend in food research is continuing today particularly in relation to brain and cardiometabolic health, given the huge burden they pose on human health, with no geographical boundaries. Currently, there is an increasing demand for 'pure' and 'clean' foods as well as potent bioactive ingredients that can promote beneficial health outcomes. Several studies, including in vitro investigations, clinical trials, and observational studies related to food and nutritional patterns have already identified, proposed, and in some cases challenged the mechanisms of action of these foods and food ingredients. The book "Food bioactives and impact on brain and cardiometabolic health findings from in vitro to human studies" has gathered innovative, high-quality research manuscripts (letters to the editor, original research and review papers) on bioactive constituents of foods and dietary patterns which can directly impact upon brain and cardiometabolic health. These manuscripts reporting on different areas of this research field, from the description of new conceptual ideas, mechanisms of action, and structural modelling to clinical trials and observational studies.